Pengaruh Kepuasan dan Kepercayaan terhadap Loyalitas Konsumen Kedelai Jepang Edamame Pendekatan Structural Equation Modeling - NIDYATANTRI, NI MADE MARTA; SURYAWARDANI, IGA OKA; AGUNG, DEWA GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract Satisfaction Influence and Loyalty Consumer Confidence in Japanese Soy Edamame. Structural Equation Modeling Approach Edamame is a product of horticultural vegetables which are not included nuts. It has a larger size than the size of soybean products. This study was conducted at CV. Bariball Agriculture . This company have business in field of Agrib u s i n e s s of Edamame product . The purpose of this study is to investigate the influence of satisfaction, trust, and loyalty consumer confidence in Japanese soy Edamame, analyze the relationship of satisfaction and trust on consumer loyalty of Japanese Soybean Edamame, and analyze the impact indicators of taste, price, coverage product, promotion, packaging product, and practical influence of customer satisfaction and believe indicator believe of products, organic products, and the benefits of the product to consumer confidence. S tructural equation modelling (SEM) was designed to understand and SPSS 22 and AMOS 22 . The result show customer satisfaction has significant influence on customer loyalty of Japanese Soybean Edamame with p = 0.038. Customer trust has significant influence on customer loyalty of Japanese Soybean Edamame with p=0.000. Customer satisfaction has a significant correlation with costumer trust with p=0,000. The result show indicators taste, price, coverage product, promotion, packaging product, and practica l has significant influence on satisfaction. Indicators are believe product, organic product, and benefit of product has significant influence on trust. Keywords: Japan soybean E damame, satisfaction, trust, loyality, SEM